Association between ambient air pollution and tuberculosis risk: A systematic review and meta-analysis. (August 2021) - Xiang, Kun; Xu, Zhiwei; Hu, Yu-Qian; He, Yi-Sheng; Dan, Yi-Lin; Wu, Qian; Fang, Xue-Hui; Pan, Hai-Feng
Abstract: There is a growing body of evidence suggesting an association between air pollution exposure and tuberculosis (TB) incidence, but no meta-analysis has assembled all evidence so far. This review and meta-analysis aimed to derive a more reliable estimation on the association between air pollution and TB incidence. PubMed, Embase and Web of Science electronic databases were systemically searched for eligible literature. The PECO framework was used to form the eligibility criteria. Effect estimates and 95% confidence intervals (CIs) published in the included studies were pooled quantitatively. Seventeen articles met the inclusion criteria. The pooled estimates showed that long-term exposure to particulate matter with an aerodynamic diameter ≤10 μm (PM10 ) was associated with increased incidence of TB (per 10 μg/m 3 increase in concentrations of PM10 : risk ratios (RR) = 1.058, 95% CI: 1.021–1.095). Besides, long-term exposure to sulfur dioxide (SO2 ) and nitrogen dioxide (NO2 ) were significantly associated with TB incidence (per 1 ppb increase, SO2 : RR = 1.016, 95% CI: 1.001–1.031; NO2 : 1.010, 95% CI: 1.002–1.017). We did not find a significant association of PM2.5, ozone (O3 ) or carbon monoxide (CO) with TB risk, regardless of long-term or short-term exposure. However, in view of the 2016 ASA Statement and the biological plausibility of PM2.5 damaging host immunity, the association between PM2.5 and TB risk remains to be further established. This meta-analysis shows that long-term exposure to PM10, SO2 or NO2 is associated with increased odds of TB, and the specific biological mechanisms warrant further research. Graphical abstract: Image 1 Highlights: This is the first meta-analysis to explore the association between major air pollutants and tuberculosis risk. Long-term exposure to PM10, SO2 or NO2 is associated with increased odds of tuberculosis. Short-term air pollution exposure will not increase the prevalence of tuberculosis. Improving air quality can ease the burden of tuberculosis to some extent.